PENGARUH INTERAKSI SOSIAL DALAM KELUARGA TERHADAP MOTIVASI BERPRESTASI ANAK PEDAGANG DIKAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Betty Sofiana Sinaga; Daeng Ayub Natuna; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the research problem is how high the socialinteraction of the children in the merchant's family, how high is the achievementmotivation of the merchant's children and how much influence is the social interactionin the family on the achievement motivation of the children of traders in Maredan BaratVillage, Tualang District, Siak Regency. The purpose of this study was to determine thelevel of social interaction of children in the merchant's family, to determine the level ofachievement motivation of the merchant's children, to determine the influence of socialinteraction in the family on achievement motivation of the children of traders inMaredan Barat Village, Tualang District, Siak Regency. This research is a type of expost facto research, a quantitative descriptive study of two variables to find theinfluence between variables. The number of samples in this study was 46 people.Descriptive statistical analysis was carried out to describe the respondent's profile datain the form of mean and standard deviation of the questionnaire results, based on thedemographics of the respondents, variables, indicators and questionnaire items, theninferential statistical analysis was used to test the previously formulated hypotheses.The results of the study showed that the level of social interaction in the family and highachievement motivation for the child traders. Furthermore, it was obtained a significantinfluence between Social Interaction in the Family (X) on Achievement Motivation (Y)for the children of traders in the village of maredan barat, Siak Regency, the biginfluence was 22.20%, because there were still 77.80% which was determined by otherfactors that were not be part of this research. This effect is illustrated by each one-unitincrease in social interaction in the family (X) followed by an increase in achievementmotivation(Y) of 1.168 one unit. With the Pearson product moment correlation valuebetween social interaction in the family and achievement motivation 0.472 and sig (2-Tailed) 0.00.Key Words: Social Interaction in the Family, Achievement Motivation and Traders' Children